Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Step-by-step explanation:
From what I know
3x-1=0
3*(-2)-1=0
-6-1=0
=-7.
I'm not sure but u can try it.
The value of f(-2) in this function is f(-2) = -7
To solve this expression, just replace 'x' with -2. When the expression is ready, let's calculate it.
First we multiply or divide, then add or subtract.
Resolution
f( x ) = 3x - 1
f(-2) = 3 · (-2) - 1
f(-2) = -6 - 1
f(-2) = -7
So, the alternative value is f(-2) = -7
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.